Yorùbá Literary Artists on Youths and Parenthood - Olufadekemi Adagbada; Olatunde Adeleye Adeyemo; Ejitoyosi O. Salami (Yoruba Studies Review)
The youths of any nation are the bedrock of her development, through viable socio-political and economic contributions. They are the indispensable agents of change that can turn the table round for better, especially in developing nations. The natural psycho-biological development of youths and young adults, living in a nation going through socio-political economic and security challenges, coupled with their being nurtured in some cases through faulty parenting, have manifested in the typology of Nigerian youths. The nation now has a high number of misguided youths who portray demeaning image about Nigeria. This study, hinged on Elkind’s (1967) constructionists’ perspective of adolescents’ cognitive development and womanists’ theory as opined by Hudson-Weems (1993) and Kolawole (1997), to the effect that the desire of the agitating African women is complementarity with men in all aspects of life. With these views; exemplified with excerpts from randomly selected Yoruba dramatic, prosaic, and poetic texts, this essay submits that improper parenting, peer group pressure, excessive drive for material wealth, unemployment, poverty, inaccessibility to social and financial aids as experienced by the youths, are some of the reasons why the future appears bleak for Nigeria. The study recommends collective responsibility by parents, to become positive role models for their children by spending undivided and qualitative time with them, thus creating a good and safe environment for their children to be free to express themselves. Corporate organizations and religious bodies should pay back to the society by organizing workshops and low-capital focused entrepreneurial seminars for the youths. Government should as a matter of urgency, put massive employment generation on priority list, ensure a drastic reduction in the years of working experience required before youths’ employment and ensure desirable remuneration for employed youths by individual and corporate bodies.